Ordered intermetallic compounds combining precious metals and transition metals for electrocatalysis - Yang, Meicheng; Wan, Jinxin; Yan, Chao (Frontiers in Chemistry, 2022)
Ordered intermetallic alloys with significantly improved activity and stability have attracted extensive attention as advanced electrocatalysts for reactions in polymer electrolyte membrane fuel cells (PEMFCs). Here, recent advances in tuning intermetallic Pt- and Pd-based nanocrystals with tunable morphology and structure in PEMFCs to catalyze the cathodic reduction of oxygen and the anodic oxidation of fuels are highlighted. The fabrication/tuning of ordered noble metal-transition metal-bonded intermetallic PtM and PdM (M = Fe, Co) nanocrystals by using high temperature annealing treatments to promote the activity and stability of electrocatalytic reactions are discussed. Furthermore, the further improvement of the efficiency of this unique ordered intermetallic alloys for electrocatalysis are also proposed and discussed. This report aims to demonstrate the potential of the ordered intermetallic strategy of noble and transition metals to facilitate electrocatalysis and facilitate more research efforts in this field.